BURDEN BEYOND HEALTH AND HEALTH CARE COMPLICATIONS: THE SOCIOECONOMIC IMPACT OF VIRAL HEPATITIS B AND C IN PAKISTAN (The Research of Medical Science Review, 2025)
Hepatitis B and C pose significant public health challenges in Pakistan, not only due to their medical consequences but also their profound socioeconomic impacts. This study examines how these chronic infections affect employment status, out-of-pocket healthcare expenditures, and the relationship between disease severity and financial burden among patients. This study finds significant effect of viral hepatitis B and C on labor productivity, labor mobility, absenteeism and presentism at work place, family income, mortality and life style in Pakistan. This study also originated significant direct relationship between total per month direct medical cost and indirect medical cost at different disease stage. Higher direct medical costs and indirect medical costs were found with advanced disease and vice versa. In the initial stage of the disease most of the direct medical costs were associated with diagnostic charges and medical services whereas the decompensated cirrhosis stage a large portion of direct medical costs were related to hospital admission and medication. Findings also indicated that individuals with advanced stages of hepatitis are more likely to face unemployment, reduced productivity, and catastrophic healthcare costs, particularly in low income households. The absence of structured support systems exacerbates these challenges, leading to a cycle of poverty and worsening health. The research underscores the urgent need for integrated health and social policies to address the broader consequences of hepatitis B and C in Pakistan